Simultaneous Ipsilateral Floating Hip and Knee: A Complex Combination and Difficult Surgical Challenge - Abdellatif Benabbouha; Mostapha Boussouga; Salaheddine Fjouji; Adil Lamkhanter; Abdeloihab Jaafar (Case Reports in Orthopedics)
Simultaneous ipsilateral floating hip and floating knee are extremely rare. To the best of our knowledge, only four cases have been described in the literature. This uncommon injury is mostly caused by high-velocity impact and associated with life-threatening lesions. We report a unique case of concomitant ipsilateral floating hip and floating knee following road traffic accident. The patient presented ipsilateral hip dislocation and acetabular, femoral, and tibial fractures associated with chest trauma. The aim of this report is to highlight the severity and rarity of this combination and to describe the therapeutic recommendations.